Intrathecal immunoreactivity in people with or without previous infectious mononucleosis. (10th June 2020) - Jons, Daniel; Zetterberg, Henrik; Malmeström, Clas; Bergström, Tomas; Axelsson, Markus; Blennow, Kaj; Thulin, Måns; Sundström, Peter; Andersen, Oluf
Abstract: Objectives: The risk of developing multiple sclerosis (MS) increases (OR: 3.1) after infectious mononucleosis (IM). However, the nature of this link is obscure. We tested the hypothesis that IM might incur long‐term sequelae, including low‐key inflammatory activity, with characteristics of an MS endophenotype (or presymptomatic trait) and that assays of MS‐relevant cyto‐/chemokines in the cerebrospinal fluid (CSF) post‐IM may show a trend in this direction. Materials and methods: We selected seven CSF cytokines (IL‐1b, IL‐6, YKL‐40, TNF‐alpha) or chemokines (IL‐8, CCL2, IP‐10), representing pro‐inflammatory factors previously associated with MS. We assayed the CSF levels of these seven cyto‐/chemokines in healthy individuals with a median follow‐up time of 10 years after serologically confirmed IM (post‐IM group, n = 22), and in healthy controls without a history of IM (n = 19). A group of MS patients (n = 23) were included as reference. Results: The CSF levels of IP‐10, YKL‐40, and CCL‐2 were higher in the post‐IM group than in our IM unexposed controls ( P  = .021, .049, .028). Seven of seven cyto‐/chemokine assays showed a trend in the predicted direction ( P of binomial ratio = .008). However, this trend was non‐significant in a multivariate test ( P  = .22). A power analysis indicated that similar studies including a larger cohort would be numerically realistic. Conclusions: These results do not reject the hypothesis that the established epidemiological association between IM and MS results from a stepwise inflammatory propagation from IM sequelae to an MS endophenotype (or presymptomatic trait) in a proportion of IM patients, pending confirmation with adequate power.